Consideraciones protésicas básicas en los implantes oseointegrados - Becerra-S., Gerardo; Botero-U., Hernán (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Clinical and experimental studies have established that osseointegrated implants are a predictable treatment modality for partially and fully edentulous patiens. The achivement of osseointegration around implants depend upon the biocompatibility of the implant material, the surgical technique, the implant bed and biomechankal factors. (Albrektsson et al, 1981). The osseointegra tion has perrnited to dentists to expand their clinical practice and to offer new options to traditional treatments for fixed and removable prosthesis (partially or fully).